PEMANFAATAN MEDIA AUDIO VISUAL DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI PENGUKURAN SUDUT PADA SISWA KELAS IVB SDN 1 PENENGAHAN - Nurashri Partasiwi; Yulita Dwi Lestari; Connyta Elvadola; Deviyanti Pangestu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to improve mathematics learning outcomes by utilizing audio-visual media in class IV B students at SDN 1 Penengahan. This type of research is classroom action research with two cycles. Each cycle consists of four stages, namely planning, action, observation, and reflection. The subjects of this study were students of class IV B at SDN 1 Penengahan for the 2022/2023 academic year, which consisted of 22 students. Prior to the study, a pre-cycle was conducted which showed only 31.8% of students scored above the KKM. After the research in the first cycle which scored above the students' KKM, which was 60%, while there was an increase in the second cycle, which was 86%. With the average posttest score of students increasing from 52.72 in the pre-cycle stage, to 66.81 in cycle I and to 82.5 in cycle II. Furthermore, the number of students who scored above the KKM has also increased, namely at the pre-cycle stage as many as 7 students, increased in cycle I to 13 students and experienced another increase in cycle II to 19 students.